Ludic strategies for the promotion of communicative competence in 9th grade efl class at liceo cristiano - Sailema Lima, Grace Irene (2017)
The influence this investigation will have on students with problems in speaking will be of great results and academic advantages for the students, teachers and the institution as well. This project consists of ludic strategies that are going to give students the opportunity to practice with meaningful exercises in which they will allow learning to take place. This and many other aspects will also provide students the maximum training in speaking in English in and outside of the classroom for them to have the adequate practice in the language. Chapter one of this project refers about the problem students from the ninth-year basic education of Liceo Cristiano has. In chapter two, the theory about fixing the problem will be addressed, giving the many aspects and foundations that will be covered and the methods, the proposal will keep students in a learning process that will help them eventually in becoming independent learners and acquiring the English language???